The supply chain management role as an economic reform to overcome the problem of regional imbalances, in Republic of Tatarstan - Askar Nailevich Mustafin; Alexander Evgenyevich Shlyakhtin; Rastislav Kotuli? (International Journal of Supply Chain Management, 2020)
Abstract— The aim of this paper is to investigate how supply chain integration affects company performance. The paper considers the supply chain role in economy and regional disproportions between regions and federal districts in the Russian Federation. In the course of the proposed economic reform (fiscal space), we discovered that within 5 years, the least developed municipal entities that are part of the subject of Russia - the Republic of Tatarstan - will be able to receive up to $ 200 thousand (US Dollars), which could become the foundation for the further socio-economic transformations in the territory, and also act as an instrument for the formation of a more favorable investment climate. These distribution effects, both across and within countries, are likely to affect trade policy, and consequently, the evolution of supply chains.